A Conceptual Review of Speaking Practice and Learner Confidence in EFL Classrooms - Devandra Raffy Nugraha; Arif Suryo Priyatmojo (Universitas Nurul Jadid, 2026)
Speaking is widely regarded as a crucial skill in English as a Foreign Language (EFL) learning; however, many learners experience difficulties in speaking due to psychological factors such as anxiety and low confidence. Although previous studies have discussed speaking skills and learner confidence extensively, their relationship is often addressed implicitly rather than through a clear conceptual explanation. This article aims to examine the relationship between speaking practice and learner confidence in EFL classrooms from a theoretical perspective. Employing a library-based and conceptual research design, this study synthesizes relevant theories, including Self-Efficacy Theory, the Affective Filter Hypothesis, and the Willingness to Communicate framework. The discussion suggests that systematic and meaningful speaking practice can serve as a source of positive learning experiences that enhance learners’ confidence and reduce affective barriers to communication. As learners’ confidence develops, their willingness to engage in speaking activities increases, creating a positive cycle between practice and confidence. This conceptual discussion provides a theoretical foundation for designing speaking activities that support both learners’ oral development and affective readiness to communicate in EFL classroom contexts.